Studies on the effect of nanosized ceramic filler in poly (vinyl alcohol)-lithium perchlorate based polymer electrolytes / Lim Chin Shen - Lim, Chin Shen (2012)
In this study, three polymer electrolyte systems are prepared by means of solution casting technique. These polymer electrolytes consist of poly (vinyl alcohol) (PVA) (host polymer), lithium perchlorate (LiClO4) (dopant salt) and different types of ceramic fillers [antimony trioxide (Sb2O3) and titanium oxide (TiO2)]. The prepared polymer electrolyte samples with various wt. % of filler content were subjected to X-ray diffraction (XRD), impedance spectroscopy, morphological, and thermal studies. 60 wt. % of PVA and 40 wt. % of LiClO4 shows the highest ionic conductivity of 2.6110-5 S cm-1 at room temperature. The highest ionic conductivity increased to 9.5110-5 S cm-1 and 1.3010-4 S cm-1 with the addition of Sb2O3 and TiO2, respectively. The prepared polymer electrolyte systems obey the Arrhenius rule. XRD analyses reveal the suppression in crystallinity of PVA upon the addition of LiClO4 and inorganic fillers. Incorporation of Sb2O3 and TiO2 shifts the glass transition temperature, Tg to a lower temperature at which the flexibility of polymer backbone was enhanced. SEM images reveal the modification of surface morphology upon the addition of LiClO4 and inorganic fillers. TGA studies indicate that the thermal stability of polymer electrolyte increases significantly when Sb2O3 and TiO2 were introduced to polymer electrolyte which results in the second onset decomposition temperature being shifted to higher temperature. Electric double layer capacitors (EDLCs) were prepared by sandwiching the polymer thin films with two carbon electrodes. Results reveal that the polymer electrolyte with fillers attains higher specific capacitance compared to polymer electrolyte without filler. The prepared EDLCs have the capacitance retention over 90% which demonstrates the EDLC cells have excellent electrochemical stability.